Impact of Management Practices on Micro and Small Enterprise (MSEs) Performance in Marinduque, Philippines - Michael V. Capiña (Research Synergy Foundation, 2021)
In the Philippines, micro and small enterprises (MSEs) comprise the largest part of the business economic undertakings and are among the most important development agents in rural communities like Marinduque. MSEs offer opportunities to poor people the possibility of earning income, training, work experience and employment. However, most of the micro and small enterprises in the country perform behind the neighboring ASEAN countries. Thus, assessing the impact of their management practices on operational functions (marketing, production, financial, human resources) and the significant relationship to MSEs performance (sales, production, and income) as the basis for government interventions. The study disclosed that management practices of 35 selected manufacturing MSEs on operational function is doing well with an overall mean of 3.70 interpreted as